Prognostic biomarker PSMD14 facilitates bladder cancer tumorigenesis and progression by regulating Nucleolin-YAP1 axis - Yunfei Wu; Zhijie Xu; Runzhe Wang; Yanfeng Bai; Xiaoyi Chen; Cheng Cheng; Baiye Jin; Guanghou Fu (Translational Oncology)
Deubiquitinating enzymes (DUBs) significantly contribute to tumor progression and treatment resistance in bladder cancer. However, the mechanisms by which DUBs promote malignant behavior in patients with bladder cancer remain poorly understood. Using online databases such as TCGA, GSE13507, and GSE23894, along with clinical sample validation, the expression profiles of PSMD14 in patients with bladder cancer were identified. The analysis revealed correlations among PSMD14, nucleolin (NCL), and YAP1, which were verified using TCGA data and clinical sample studies. In this study, PSMD14 was identified as a novel DUB involved in bladder cancer malignancy. PSMD14 expression is upregulated in the tissues of patients with bladder cancer and is associated with poor clinical outcomes. Both in vitro and in vivo experiments demonstrated that PSMD14 inhibition significantly reduced bladder cancer cell proliferation, metastasis, and cisplatin resistance. Mechanistic investigations revealed that PSMD14 enhances protein stability and NCL expression through deubiquitination. NCL, an RNA-binding protein, exerts oncogenic effects in patients with bladder cancer by binding to and stabilizing YAP1 mRNA, leading to increased YAP1 expression and activation of downstream YAP1-related pathways. Notably, the tumor-suppressive effects of PSMD14 inhibition were partially reversed by the overexpression of either NCL or YAP1. In conclusion, the PSMD14/NCL/YAP1 axis plays a pivotal role in the malignant behavior of bladder cancer, including proliferation, metastasis, and chemoresistance. These findings suggest that PSMD14 is a critical biomarker for predicting bladder cancer prognosis and is a potential target for therapeutic interventions.